Φιλολογικά πορτραίτα : 1886-1920 - Ταγκόπουλος, Δημήτριος, 1867-1926 ([χ.ό.], 1922)
Ραμπαγάς -- Γαβριηλίδης -- Μητσάκης -- Κρυστάλης -- Παπαδιαμάντης -- Ροϊδης-- Παλαμάς -- Νιρβάνας -- Ξανόπουλος -- Μαρκοράς -- Ο Νουμάς